Factors associated with longer brain metastasis-free survival in limited-disease small-cell lung cancer who underwent concurrent chemoradiotherapy, a retrospective analysis - Zhao, Xiang-Rong; Li, Jia; Zhang, Zhen; Gao, Chao; Yang, Zheng-Qiang (Frontiers in Oncology, 2026)
IntroductionThis study aimed to explore the limited-disease small-cell lung cancer (LD-SCLC) patients who were treated with concurrent chemo-radiotherapy (CCRT) without prophylactic cranial irradiation (PCI), and evaluated the possible risk factors for BM development in this population.MethodsThis study was a retrospective study which reviewed 182 patients treated with CCRT for stages I-III and who finally developed brain metastases (BM) between 2017 and 2021 were reviewed to elucidate the risk factors for BM.ResultsIn this study, N descriptors at initial SCLC (N3, 5.9 points; N2, 3.1 points; N1, 1.5) and response of primary tumor (PT) to CCRT (NR 4.7; PR 1.0) were most strongly associated with BM-free survival. Based on these factors, patients were stratified as low risk (4.0 or fewer total points), moderate risk (4.1 to 8.0 points), and high-risk (more than 8.0 points), and the median BM-free survival was 24 months, 16 months, and 8 months, respectively, with 12-month BM-free survival of 91.7%, 66.3%, and 25.0%, respectively (P <0.001).DiscussionOur results demonstrate that N descriptors and remission grade of the primary tumor after CCRT were significantly correlated with the incidence of BM.